1995
DOI: 10.1021/bi00002a030
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Study of the pH-Dependent Interaction of Chromogranin A with an Intraluminal Loop Peptide of the Inositol 1,4,5-Trisphosphate Receptor

Abstract: The secretory vesicles of adrenal chromaffin cells have previously been identified as a major inositol 1,4,5-trisphosphate (IP3)-sensitive Ca2+ store, and their Ca2+ store role has been attributed to the presence of chromogranin A, a high capacity, low affinity Ca2+ binding protein. Chromogranin A has since been shown to exist primarily in a dimeric state at pH 7.5 and primarily in a tetrameric state at the intravesicular pH of 5.5 and has also been shown to interact with the membrane proteins of secretory ves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 28 publications
0
39
0
Order By: Relevance
“…Affinity constants were derived by Scatchard analysis or by non-linear curve fitting of the standard Langmuir binding isotherm (A ϩ B 7 AB). Thermodynamic data were obtained by fitting to the affinity data the non-linear form of the van't Hoff equation (50).…”
Section: Methodsmentioning
confidence: 99%
“…Affinity constants were derived by Scatchard analysis or by non-linear curve fitting of the standard Langmuir binding isotherm (A ϩ B 7 AB). Thermodynamic data were obtained by fitting to the affinity data the non-linear form of the van't Hoff equation (50).…”
Section: Methodsmentioning
confidence: 99%
“…2B) (533). In vitro binding studies showed that the CGA-InsP 3 R interaction was promoted by acidic pH, as would be experienced in the lumen of a mature secretory vesicle, while the CGB-InsP 3 R interaction was pH independent (532)(533)(534). Incorporation of CGA into liposomes containing purified InsP 3 R enhanced InsP 3 -mediated Ca 2ϩ release (532).…”
Section: Chromograninsmentioning
confidence: 97%
“…Equilibrium thermodynamic parameters were obtained by measuring the dissociation constant over a range of temperatures (5-37°C) and fitting the thus determined binding free energy ⌬G to the nonlinear form of the van't Hoff Equation 1 (22).…”
Section: Surface Plasmon Resonance Measurements Of Equilibrium Bindingmentioning
confidence: 99%